The deformation mechanism in the western Qiangtang terrane and its surroundings: evidence from magnetotelluric data - Gu, Jiangfan; Jin, Sheng; Dong, Hao; Wei, Wenbo; Ye, Gaofeng; Zhang, Letian (Frontiers in Earth Science, 2023)
Located in the central part of the Tibetan Plateau, the Qiangtang terrane preserves important record of the uplift and deformation history of the Plateau, and therefore remains an attractive area of research. However, deep geophysical investigations of its western part are still limited. To further understand the deep structure of the western Qiangtang terrane and its surroundings, we use magnetotelluric array data to generate a 3D electrical structure. It reveals high resistivity anomalies in the upper crust and scattered high conductivity anomalies in the mid-lower crust. The electrical structure also suggests that the Longmu Co-Gozha Co fault once believed to be a major regional deformation boundary, may not have cut through the crust. The melt content and rheological parameters derived from the electrical structures show dominant ductile-type deformation in most of the study area, which contributes to block extrusion along the slip faults. Viscous deformation regions formed by mantle melt upwelling in the mid-lower crust may contribute to the formation of the N-S directed normal faults on the surface.